Performance and physical activity. How playful activities implemented into training in Danish esports clubs influence players' performance experience - Østergaard, Lars Domino; Straszek, Christian Lund Nørgaard; Frandsen, Lasse Nørgaard (Frontiers in Sports and Active Living, 2024)
Introduction Over the past few years, attention has focused on how physical activity can enhance esports players' performance. For example, complementing esports training with physical activities has been explored. However, most of these activities are based on traditional strength or endurance-related exercises, which do not align with the interests of children attending organized esports clubs. Methods In this study, we investigate playful physical activities. Our research is based on qualitative pilot studies, where we observed and interviewed players (N = 77) and coaches (N = 12) from nine organized esports clubs for two to four months per club. We explored their experiences with playful physical activities implemented during esports training. Using a reflexive thematic analytical approach, we revisited and analyzed the data. Results The results are presented in this paper as three nonfictional short stories, creatively describing the lived experiences of the players and coaches. We emphasize patterns of shared meaning and identify the “What's” and “How's” associated with esports training when playful physical activities are incorporated. Despite differences in form, duration, and intensity compared to activities referenced in the literature on esports and performance, our results demonstrate that playful activities positively influence esports players' skills and performance. Discussion Furthermore, our findings suggest that playful physical activities, as opposed to traditional strength and endurance exercises, often associated with physical activity, are acceptable for esports coaches. However, for maximum impact, these activities must be relevant and directly related to the games played in the esports clubs. Based on our research, we recommend implementing playful physical activities that align with the actual esports training to support developing and optimizing players' esports skills and performance.